2015
DOI: 10.1103/physrevlett.115.183401
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Positronium Annihilation with Electric Fields

Abstract: We show that the annihilation dynamics of excited positronium (Ps) atoms can be controlled using parallel electric and magnetic fields. To achieve this, Ps atoms were optically excited to n ¼ 2 sublevels in fields that were adjusted to control the amount of short-lived and long-lived character of the resulting mixed states. Inclusion of the former offers a practical approach to detection via annihilation radiation, whereas the increased lifetimes due to the latter can be exploited to optimize resonance-enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…5). Figure 9 shows the results of experiments in which a UV laser (λ = 243.01 nm) was used to excite Ps atoms in a 13 mT magnetic field B with applied parallel electric fields F with strengths up to ±3 kV cm −1 [129,130] (see Fig. 8).…”
Section: Stark and Zeeman Effects In N = 2 Psmentioning
confidence: 99%
See 3 more Smart Citations
“…5). Figure 9 shows the results of experiments in which a UV laser (λ = 243.01 nm) was used to excite Ps atoms in a 13 mT magnetic field B with applied parallel electric fields F with strengths up to ±3 kV cm −1 [129,130] (see Fig. 8).…”
Section: Stark and Zeeman Effects In N = 2 Psmentioning
confidence: 99%
“…For Rydberg production an infra-red (IR) laser (≈8 mJ, ∆ν = 5 GHz, λ ≈ 750 nm) is used to drive 2 3 P → n 3 S/n 3 D transitions. This excitation process couples the ground state atoms to the S or D character of excited Stark states, whose azimuthal quantum number can be controlled via the UV and IR laser light polarizations [125,129].…”
Section: Excitation Of Rydberg Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Having shown that existing measurements are too imprecise resolve this splitting, one can ask about the future prospects. Upcoming experiments at University College London plan to remeasure the n = 2 fine-structure with a reduced uncertainty yielding ∆ 2,P ∼ 100 kHz [36][37][38]. A measurement of ∆ 2,P would require only a factor of two improvement.…”
mentioning
confidence: 99%